Production and nutrient content of earthworm casts in a tropical agrisilvicultural system - Norgrove, L.; Hauser, S. (Elsevier, 2000)
Earthworm surface cast production and nutrient turnover through casts were measured for 3 years in a 17-year-old timber plantation in southern Cameroon after selective reduction to two timber stand densities (TSDs) and understorey cropping with plantain and tannia. Neither understorey cropping nor timber stand density treatments had significant effects upon cast production in any year. Mean cast production in cropped plots was 35.7 Mg ha−1in the first year, 34.9 Mg ha−1 in year 2 and 30.1 Mg ha−1 in year 3. This was 63%, 84%, and 65%, respectively, of cast production in undisturbed, unthinned timber plantation plots. In comparing cast nutrient concentrations between years 1, 2 and 3, there were highly significant correlations for nearly all nutrients in control plots but fewer such correlations in the low TSD. In cropped plots, none of earthworm parameters was correlated with nutrient concentrations of slash or amounts of slash applied to the soil surface at establishment. There were positive correlations between cast N and litterfall N (kg ha−1 y−1) in both year 2 (cast N = 0.49 × litterfall N + 61.7, r2=0.46) and year 3 (cast N = 0.38 × litterfall N + 55.6, r2=0.42). The ratio of soil:cast nutrient concentrations were related by negative power functions to soil nutrient concentrations for all nutrients and organic carbon. This suggests that earthworm communities adjust to lower soil nutrient concentrations by increasing their selectivity and thus produce relatively higher quality casts on poorer soil.